The ‘Son of God’ in the Gospel of John and its relevance for Muslim-Christian dialogue - Rashid, Ungaran; Harlan, Mark (2021)
The term “son of God” has been a source of confusion and controversy in the history of Christian-Muslim encounters. Christian tradition regards the gospel according to John as the account which most clearly portrays the deity of Christ and points to his being the “son of God” as proof of his divinity and equality with God. This paper presents a Muslim scholar’s challenge to this understanding, arguing that the “son of God” in John’s Gospel refers to an anointed king (messiah), who, as heir of the Davidic kingdom, has authority to act as God’s surrogate on the earth. The equality of the son does not refer to a divine nature but his being God’s unique agent possessing full authority from God. It is not a claim to be on par with God or an incarnation of God. In response a Christian scholar agrees, however, additional issues impact interpretation (e.g., the nature of Hebrew monotheism, Hebrew and Greek worldview differences, the semantic range of terms for God, the son’s total obedience as a revelation of God and Jesus’ identity as the Word of God). Questions over the inner life of God reflected in Christian Trinitarian discussions and Muslim kalam debates, though related, are a different matter (in which there is, nevertheless, a surprising measure of common ground). Several implications for Muslim-Christian dialogue will be offered.